The adventures of Tom Sawyer - Twain, Mark, 1835-1910 ([Boston, Mass] : Thomson Heinle, 2007)
Join Tom Sawyer and his friends in a series of fantastic adventures: forming secret societies, pretending to be pirates, attending their own funerals, and even solving a murder. Travel down the Mississippi River to a small town in Missouri where each day brings a new adventure and find out just how exciting a boy's life can be
Title from container
Keywords: Sawyer, Tom (Fictitious character) -- Fiction; Boys -- Missouri -- Fiction; Adventure and adventurers -- Fiction